OPTIMALISASI PARAMATER RESISTANCE SPOT WELDING UNTUK PENGELASAN TIGA TUMPUK LEMBAR BAJA SPCC - Pradipta Satrio Wibisono (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
In the automotive industry, the latest breakthroughs and innovations are strongly influenced bymaintaining and increasing production results so that the use and application of technology is anabsolute must, as is welding technology. Thin sheet-shaped components are found in many car bodies.One of the methods used in joining plate sheets is to use the resistance spot welding method, which is awelding process that is only carried out at a certain point using copper electrodes. In the welding method,maintaining quality in order to produce products and services that can meet the needs and expectationsof consumers related to the product's life time or service. SPCC steel (Cold Roller Stell Sheet) is one ofthe most widely used materials in car body welding applications. The characteristics and mechanicalproperties of SPCC steel from the results of the three-sheet welding were examined using the parametersof welding current, welding time, welding distance. The results showed that the increase in current wouldaffect the diameter of the electrode traces and the nuggets that were formed. The greater the current used,the larger the diameter of the trail, so that the optimum pull-shear load is at a current of 6.5 kA at adistance of 20mm with a value of 365.53 MPa, also the highest hardness value is in the nugget area witha hardness value of 595, 14 HVN at a current of 6.5 kA and from the results of measuring grain diameterin microstructural testing for the HAZ area the best at a welding current of 6.5 kA. Because the smallerthe weld grain diameter, the greater the strength of the weld joint. Then the data from the results of theshear-shear test are analyzed using the Taguchi method, and the most effective parameters in the tensilesheartest with a combination of A (6.5) B (1.5) C (15) and from the experimental results for tensile loads.slide obtained 397 MPa.